The Role of Principals’ Collaborative Leadership in Developing the Seven Habits of Great Indonesia Children at SDN Petarangan - Ardita Rizky Amalia; Meirina Nugraheni; Tri Wahyuni; Nurkolis (Educia Journal, 2026)
This study analyzes the role of the principal’s collaborative leadership in developing the Seven Habits of Great Indonesian Children at SDN Petarangan. The study was grounded in the need to strengthen character education through school culture, stakeholder participation, and consistent habituation practices at the elementary school level. A qualitative approach with a descriptive case study design was employed to obtain an in-depth understanding of leadership practices in their natural school context. Data were collected through observation, in-depth interviews, and documentation involving one principal, five teachers, one educational staff member, and one chairperson of the school committee. The data were validated through source and technique triangulation and analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings show that the principal implemented collaborative leadership through open communication, regular coordination, shared decision-making, teacher coaching, role modeling, parental involvement, and collective evaluation. The Seven Habits program was implemented through daily habituation activities, including morning greetings, discipline routines, classroom cleanliness, literacy activities, group cooperation, religious activities, and polite behavior. These activities supported the development of students’ discipline, responsibility, independence, cooperation, social care, creativity, and integrity within daily school life and broader school community relationships. However, the implementation still faced challenges, including inconsistent student habituation, limited parental involvement, and time constraints between academic targets and character-building activities. The study concludes that collaborative principal leadership functions as a strategic mechanism for building a sustainable character-based school culture through stakeholder engagement, shared responsibility, and continuous character habituation practices.